Consumer Behavior Factors and Retail Mix Factors Influencing Purchase Decision Making on EVEANDBOY - Boonmee, Jaruwan; Prasertchuwong, Weerasak (Journal of Humanities and Social Sciences, Rajapruk University, 2024)
This research objectives were to study: 1) the personal factors which influencing the decision of purchasing products in EVEANDBOY 2) the factors of consumer behavior that influence the decision to buy products in the store, and 3) the factors of retail mix that influencing decision making in the store. The sample group consisted of 400 customers of who have purchased the products and used the services at EVEANDBOY shop. The research instrument was a questionnaire with the reliability score of alpha coefficient at 0.91. The data were analyzed by using frequency, percentage, mean, standard deviation, One-way ANOVA and multiple regression analysis. The results of the research showed that personal factors on gender differences affect the different purchasing decisions of products at EVEANDBOY shops at a statistical level of .05. In addition, retailing mix factors by sorting the regression coefficient in descending order which is comprised of price, customer service, store ambience, store location, communication with customer, and merchandise assortments affects the purchasing decision of products at EVEANDBOY shops (EVEANDBOY) at a statistically significant level of .05 with predictive power of 37.9%.